Development of KPIs for an Innovation Initiative between Big Pharma and SMEs. A case study of AstraZeneca’s BioVentureHub - Lindenmeyer Asadi, Amanda; Stenbom, Malin (My University, 2020)
Global health challenges are in constant need of improvement. The life expectancy and the population is growing, nevertheless, a huge amount of the population dies prematurely of noncommunicable diseases creating a need for new innovative treatments. The life science industry faces two big challenges when trying to create innovative treatments; the difficulty in finding funding, infrastructure and laboratories for small and medium-sized enterprises, and the struggle in constantly innovating and bringing NewMolecular Entities to the market for Big Pharma companies at the same time as the cost for treatment is increasing. One initiative created aiming towards helping these actors to catalyze innovation through collaboration is AstraZeneca's BioVentureHub. Thethinking behind the hub is to create an environment where small and medium-sized enterprises and a Big Pharma company are co-located and experts within the area have the opportunity to interact with each other and share competence. The goal is to increasethe number of collaborations and facilitate a dare to share culture between the actors. The BioVentureHub has existed since 2014, and there is a big interest in understanding the results and outputs from this innovation initiative, and what Key Performance Indicators that are suitable when evaluating an organization like this. In order to investigate what value that has been captured from catalyzing innovation, a literature review and a case study has been conducted including interviews with the key stakeholders of the hub. The findings from the interviews resulted in six categories covering what the stakeholders perceive as the most valuable with the BioVentureHub; Company growth, infrastructure, competence, community, attractiveness, and collaboration. Combining these categories with existing literature within traditional measurement frameworks, innovation-and collaboration performance frameworks resulted in a recommendation of 15 Key Performance Indicators to use in collaborative innovation initiatives between a Big Pharma company and small and medium-sized enterprises. In order to further exemplify the Key Performance Indicators, both hard and soft metrics have been suggested to give a holistic and honest view of the organization. The authors believe that these proposed measurement variables will help this organization and similar ones in understanding what processes are needed in order to create an environment where innovation is catalyzed.
Keywords: Innovation; Collaboration; Big Pharma; BioVentureHub; SMEs; Performance measurement; Value Capture; Life Science; KPI; Open innovation